Dinámica estacional de las comunidades de aves en el matorral submontano de la Sierra de San Carlos, Tamaulipas, México - Gómez-Moreno, Vannia del C.; Gónzalez-Gaona, Othón J.; López-Mancilla, Alejandra; Montoya-Cruz, Lorenza; Vela-Puga, José J.; Niño-Maldonado, Santiago (Instituto de Ecología, A.C., 2022)
In Mexico, scrub habitat occupies 29.7 % (576,747 km²) of the country's surface. These areas serve as refuges for birds. However, despite their importance, the abundance and composition of birds are unknown, especially in the submontane scrub. The objectives of this work are: 1) to describe the avifaunal composition of the submontane scrub of the northwestern part of Tamaulipas, Mexico, in terms of richness, abundance, and diversity; 2) to analyze the trophic guilds that occur in the scrub as a function of seasonal variation; and 3) to determine the conservation status and endemism of bird species. For this, 12 monthly visits were made from February 2019 to January 2020, during which we identified 1,858 individuals belonging to 12 orders, 26 families, and 93 species. The richest families were Cardinalidae and Parulidae. While the most diverse season of the year was spring (H’= 3.68). Two globally endangered species and two endemic species were identified for Mexico. In addition, three species not previously recorded in the region are reported. This work is the first to report the composition and richness of birds for the northwestern part of Tamaulipas, Mexico. This highlights the importance of the submontane scrub as a refuge for migratory and resident birds. In addition, it contributes to the knowledge of regional diversity.